Gravity assessment of the impact of alliances on bilateral trade: A comparative analysis of ECOMOG and NATO. (4th February 2021) - Azu, Nnanna P.; Atta Mills, Ebenezer Fiifi Emire; Akanegbu, Benedict N.
Abstract: The prevailing notion for this research is anchored on determining the magnitude of alliances as trade determinants. Alliances are segregated into defence pact, non‐aggressive alliance and entente, which additionally integrates as trade cost in a gravity model. The Poisson pseudo maximum likelihood technique is adopted for the analysis with country pair‐effects exploited. Even though literature acknowledged three different kinds of alliance formation, the homogenous effects as trade cost have not been previously examined. Authors found that alliances' response to bilateral trade is homogenous irrespective of conceptualization and operationalism. All categories of alliance positively influence bilateral trade but could be more effective as trade determinant when rooted in a regional trade agreement. The result is more convincing in the NATO sample than the ECOWAS sample, which could not be unconnected with the level of economic and technological development in both cases. Militarized inter‐state conflict should be discouraged irrespective of the cause due to its negative effect on bilateral trade, especially in the region of its occurrence.